Made to Order: A Preliminary Review of Crime Risk Assessments in New South Wales, Australia - Groot, C. P. G. M. de (2011)
In 2001, guidelines were introduced in New South Wales (NSW) to ensure that proposed developments/redevelopments of the built environment reflected key crime prevention through environmental design (CPTED) principles. The guidelines state that in certain circumstances a crime risk assessment report is required on the proposed development. To date, these guidelines have not been evaluated, making it impossible to assess their impact and the utility of the associated crime risk assessment reports. Partially to address this gap, a small number (four) of publicly available crime risk assessment reports have been reviewed and key issues highlighted here. In particular, the relevance of some aspects of these reports is questioned, as is the impact of the relationship between the client (i.e. developer) commissioning the report and the ‘independent’ consultant. The small sample of risk assessment reports reviewed here cannot be considered representative of the larger body of such reports. Further research is required to determine the veracity of the findings of this small review.Sydney Institute of Criminology; School of Social Sciences at the University of Western Sydne